PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA SD MELALUI PENERAPAN MODEL KOOPERATIF TIPE NHT DENGAN METODE DRILL TERINTEGRASI PENDEKATAN DEEP LEARNING - Elsa L. Tampani; Alon O. Ledoh; Apriliani Kartini; Falentina Bone; Felviansi F. Ensa; Daniel W. Fointuna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to determine the presence and extent of improvement in mathematics learning outcomes of elementary school students through the cooperative learning model of Numbered Heads Together (NHT) integrated with the drill method and deep learning approach. The deep learning approach is applied to encourage higher-order cognitive processes through groupdiscussions and repeated exercises. The research design used is a pre-experimental one-grouppretest-posttest design. The sample consisted of 35 students (30 regular students and 5 inclusive students). The data analysis techniques employed were tests of normality and homogeneity. For inclusive students, the normality and homogeneity tests for pretest and posttest were satisfied, and the paired sample test indicated improvement. For regular students, the normality tests for pretest and posttest showed non-normal variance but homogeneity. Due to non-normal data, the Wilcoxontest was used, which showed an increase in student learning outcomes. The cooperative learningmodel of NHT with drill method and deep learning approach is effective in significantly improving mathematics learning outcomes for both regular and inclusive students at SD Negeri Palsatu, Kota Kupang.